TINJAUAN HISTORIS TENTANG HUBUNGAN LAMPUNG DENGAN BANTEN DI BIDANG POLITIK DAN EKONOMI DALAM PERKEMBANGAN MASYARAKAT LAMPUNG PADA ABAD 16-18 M - Danil Fajarudin; Sumiyatun Sumiyatun (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The problem in this study is that the relationship between the people of Lampung and Banten influenced the development of the Lampung community in the 16-18 century AD. The purpose of this study was to describe the relationship between the Lampung community and Banten in the political and economic fields in the development of the Lampung community in the 16-18 century AD. The usefulness of this research is that the results of this study are expected to be useful as a review in understanding the relationship between the people of Lampung and Banten in the political and economic fields in the development of Lampung society in the 16-18 century AD.